The Public Sector Premium and the Gender Gap in Latin America: Evidence from the 1980s and 1990s - Ugo Panizza (Inter-American Development Bank, Research Department, 2000)
This paper exploits a rich collection of household surveys to investigate the wage differential between the public and private sectors in 17 Latin American countries during the 1980s and 1990s. The paper also studies how the sector of employment affects the gender wage gap. The paper finds very small premia for male workers and large and significant premia for female workers. The paper also finds that, on average, Latin American women earn 30 percent less than men with similar skills and that approximately one third of this gender gap results from lack of access to formal sector employment.
Keywords: 330; Lohnstruktur; Öffentlicher Sektor; Privatwirtschaft; Fraueneinkommen; Lohnstruktur; Lateinamerika